2016
DOI: 10.2196/mhealth.4225
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Commercially Available Wearable Activity Trackers Among Adults Aged Over 50 and With Chronic Illness: A Mixed-Methods Evaluation

Abstract: BackgroundPhysical inactivity and sedentary behavior increase the risk of chronic illness and death. The newest generation of “wearable” activity trackers offers potential as a multifaceted intervention to help people become more active.ObjectiveTo examine the usability and usefulness of wearable activity trackers for older adults living with chronic illness.MethodsWe recruited a purposive sample of 32 participants over the age of 50, who had been previously diagnosed with a chronic illness, including vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
314
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(348 citation statements)
references
References 69 publications
(59 reference statements)
30
314
3
1
Order By: Relevance
“…Two focus groups were conducted in February and two others in May to account for seasonal effects on physical activity [36]. At the end of the sessions, participants were given an activity tracker, Garmin Vivofit 2, for two weeks in February and four weeks in May and then returned for follow-up focus groups.…”
Section: Focus Groups With Wat Non-usersmentioning
confidence: 99%
See 1 more Smart Citation
“…Two focus groups were conducted in February and two others in May to account for seasonal effects on physical activity [36]. At the end of the sessions, participants were given an activity tracker, Garmin Vivofit 2, for two weeks in February and four weeks in May and then returned for follow-up focus groups.…”
Section: Focus Groups With Wat Non-usersmentioning
confidence: 99%
“…Previous studies have explored activity tracker use mostly at the initial stages of use [3,7,[36][37] and have not systematically evaluated the spectrum of features used, liked, and wanted by adults aged 65 and older.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…Several studies in the past three years [e.g., 6,7,10,11] have focused on how different groups of users perceive and interact with the affordances of activity tracking devices. For example, recent studies have explored older adults' acceptance of and experiences with activity trackers [12,13]. Fritz et al [7] studied how users' practices surrounding an activity tracker evolve over long periods of use.…”
Section: Related Researchmentioning
confidence: 99%
“…Various studies have used and validated activity trackers to measure PA in both healthy controls [88,89] and CKD patients [90][91][92] and showed that this objective measure is more accurate than self-reported PA by questionnaires, which often over-or underestimates a patients' PA level [93]. Studies of Mercer et al demonstrated that even in older adults with a chronic illness, PA increased after wearing an activity tracker [94,95]. But, appropriate behavior changing techniques, such as individual goal setting and feedback on performance, suitable for elderly should be incorporated in the trackers [94,95], and proper support with regard to setting-up the trackers and interpretation of the data should be provided [94].…”
Section: Pa Monitoring and Stimulation (10/23)mentioning
confidence: 99%
“…Studies of Mercer et al demonstrated that even in older adults with a chronic illness, PA increased after wearing an activity tracker [94,95]. But, appropriate behavior changing techniques, such as individual goal setting and feedback on performance, suitable for elderly should be incorporated in the trackers [94,95], and proper support with regard to setting-up the trackers and interpretation of the data should be provided [94].…”
Section: Pa Monitoring and Stimulation (10/23)mentioning
confidence: 99%